Architecture design of a user-orientated electronic laboratory notebook: A case study within an atmospheric chemistry community - Zaki Z.M.; Dew P.M.; Lau L.M.S.; Rickard A.R.; Young J.C.; Farooq T.; Pilling M.J.; Martin C.J. (2024)
Indexed by WOS/ Scopus